The Constructive Implementation of Habit Formation and Learning Motivation to The Students’ Verb Mastery: English - Muzhir Rinaldi; Mulyadi; Hanni Yukamana (Prodi Tadris Bahasa Inggris, 2024)
Learning English is still an optional subject in Indonesian elementary schools. This is happening in some elementary schools which is determined by each school independently. According to this policy, English is only a subject that complements the management of the curriculum. Another effect is that English learning activities in the classroom result in lessons that place less emphasis on skill acquisition. Of course, this also affects students' lack of ownership of their skills. At the advanced level, students become increasingly confused about English, which was their chosen subject at the previous level. At this level, they encounter increasing difficulties. The study aims to create positive study habits that can be used as a guide for students to acquire desired competencies and as a preparation tool for students to reduce learning difficulties. The goal of learning English is to know the student's vocabulary, especially the range of basic verbs. and how much basic vocabulary do students know of verbs. This is intended to help them understand the context of learning English. It also makes it easier for students to write simple sentences in English. The researcher here uses verb as a variable to limit the study to avoid expanding the analysis. In this way, the extent of the habit formation effect of the verb can be measured. This study used an experimental design and was quantitative in design. 60 junior high school students from Al-Ittifaqiah Indralaya took part in the research study. In replacement of a two-way ANOVA, the data was examined using descriptive statistics, the normality and homogeneity test, the Wilcoxon test, the Mann Whitney U test, and the Kruskal Wallies test. The study's findings demonstrated the effectiveness of habit development in the teaching and learning process and the creation of positive habits.it is notably in mastering the vocabulary (verbs)to the seventh’ grade students of Al -Itiifaqiah Junior high school.